Eddy current methodology in the non-direct measurement of martensite during plastic deformation of SS316L - Kukla Dominik; Kondej Adam; Jończyk Sylwester; Lasota Piotr; Tabin Jakub; Schob Daniela; Roszak Robert; Kawałko Jakub; Zagórski Andrzej; Kopec Mateusz (Open Engineering)
This study examines the use of various eddy current induction techniques to evaluate the stability of austenite in SS316L steel subjected to plastic deformation. This deformation, which occurs locally in austenitic steel structures under operational loads, leads to a martensitic transformation. This transformation affects both the mechanical and magnetic properties of the steel. The martensitic phase content, being ferromagnetic, can be quantitatively assessed using a ferritoscope and other magnetic induction methods. The research explores techniques based on the analysis of impedance signal changes obtained using the NORTEC defetoscope and the WIROTEST device developed by the author’s team. By examining the phase angle, ET signal amplitude, and resonance frequency changes in the eddy current excitation system, the study aims to quantitatively assess the martensitic phase content in samples subjected to plastic deformation. These results were verified through comparison with data from a ferritoscope and X-ray diffraction analysis. Additionally, the eddy current technique facilitates surface screening of the specimen, making it possible to identify cracks and locate the martensitic transformation front in areas of stress concentration.